2023
DOI: 10.1002/fft2.302
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology and experiment indicated that medicinal food homologous components play important roles in insomnia

Xiao Xu,
Yang Liu,
Xueqi Fu
et al.

Abstract: Insomnia refers to a subjective experience where insufficient sleep duration and quality affect daytime social functioning. This study aims to screen bioactive components with medicinal food homologous (MFH), such as quercetin, beta‐sitosterol, kaempferol, stigmasterol, and capsaicin, which can treat insomnia and demonstrate that quercetin acts as a direct inhibitor of insomnia‐related glucosylceramidase and as an insulin receptor tyrosine phosphatase inhibitor in the upstream insulin signaling pathway, affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…These pathways involve the adherens junction, insulin resistance, and chemical carcinogenesis-reactive oxygen species (Figure 6). Experiments have confirmed that quercetin is an effective inhibitor of PTP1B [50]. Therefore, we speculate that kaempferol, as a structural analog of quercetin, may play a similar role to quercetin and can be combined with gut microbiota to intervene in AD and T2DM.…”
Section: Molecular Dockingmentioning
confidence: 68%
“…These pathways involve the adherens junction, insulin resistance, and chemical carcinogenesis-reactive oxygen species (Figure 6). Experiments have confirmed that quercetin is an effective inhibitor of PTP1B [50]. Therefore, we speculate that kaempferol, as a structural analog of quercetin, may play a similar role to quercetin and can be combined with gut microbiota to intervene in AD and T2DM.…”
Section: Molecular Dockingmentioning
confidence: 68%